Engineering of NIR fluorescent PEGylated poly(RGD) proteinoid polymers and nanoparticles for drug delivery applications in chicken embryo and mouse models. Issue 57 (16th September 2020) - Hadad, Elad; Rudnick-Glick, Safra; Grinberg, Igor; Yehuda, Ronen; Margel, Shlomo
Abstract : Synthesis of NIR/ICG PEGylated poly(R D GD) proteinoid NPs and their drug delivery towards mCherry-labeled 4T1 tumor. Abstract : Proteinoids are non-toxic biodegradable polymers based on thermal step-growth polymerization of natural or synthetic amino acids. Hollow proteinoid nanoparticles (NPs) may then be formed via a self-assembly process of the proteinoid polymers in an aqueous solution. In the present article polymers and NPs based on d -arginine, glycine and l -aspartic acid, poly(R D GD), were synthesized for tumor targeting, particularly due to the high affinity of the RGD motif to areas of angiogenesis. Near IR fluorescent P(R D GD) NPs were prepared by encapsulating the fluorescent NIR dye indocyanine green (ICG) within the formed P(R D GD) NPs. Here, we investigate the effect of the covalent conjugation of polyethylene glycol (PEG), with different molecular weights, to the surface of the near IR encapsulated P(R D GD) NPs on the release of the dye to human serum due to bio-degradation of the proteinoid NPs and on the uptake by tumors. This work illustrates that the release of the encapsulated ICG from the non-PEGylated NPs is significantly faster than for that observed for the PEGylated NPs, and that the higher molecular weight is the bound PEG spacer the slower is the dye release profile. In addition, in a chicken embryo model, the non-PEGylated ICG-encapsulated P(R D GD) NPs exhibited a higher uptake in the tumor region in comparison to the PEGylated ICG-encapsulated P(R D GD) NPs. However, in a tumor xenograft mouse model, which enables a prolonged experiment, the importance of the PEG is clearly noticeable, when a high concentration of PEGylated P(R D GD) NPs was accumulated in the area of the tumor compared to the non-PEGylated P(R D GD). Moreover, the length of the PEG chain plays a major role in the ability to target the tumor. Hence, we can conclude that selectivity towards the tumor area of non-PEGylated and the PEGylated ICG-encapsulated P(R D GD) NPs can be utilized for targeting to areas of angiogenesis, such as in the cases of tumors, wounds or cuts, etc.